2011
DOI: 10.1097/jom.0b013e31822cff63
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Injury Surveillance Using the Washington State Trauma Registry

Abstract: Capturing industry and occupation would enhance utility for occupational injury surveillance and research. Trauma registry data could contribute to prevention planning/evaluation, improve case ascertainment for severe occupational injuries, and aid identification of high-risk populations and emerging trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 32 publications
1
32
3
Order By: Relevance
“…Records were deduplicated and consolidated as reported in an earlier publication (because of transfers of care, many injuries were reported by more than one hospital). 8 When data for the same injury varied by report, we assumed that the most comprehensive trauma care hospital (ie, highest trauma designation level) provided the most reliable report, per the advice of WTR staff. For detailed information about the contents of each WTR field, the reader is referred to the WTR data dictionary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Records were deduplicated and consolidated as reported in an earlier publication (because of transfers of care, many injuries were reported by more than one hospital). 8 When data for the same injury varied by report, we assumed that the most comprehensive trauma care hospital (ie, highest trauma designation level) provided the most reliable report, per the advice of WTR staff. For detailed information about the contents of each WTR field, the reader is referred to the WTR data dictionary.…”
Section: Discussionmentioning
confidence: 99%
“…The WTR is described in more detail in an earlier related publication. 8 The Department of Health designates trauma services as part of the comprehensive statewide emergency medical services and trauma care system. Mandatory reporting began in 1995, and trauma coverage gradually increased as the trauma system added new hospitals.…”
Section: Study Population and Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Forst et al, 17 Sears et al, 18,19 and Husberg et al 20 have described their occupational injury surveillance research using trauma registries in Illinois, Washington, and Alaska, respectively. Interestingly, Sears et al 19 found that 46.4% of work-related injuries indicated solely by external cause of injury codes (E-codes) occurred on the nonresidential area of a farm; therefore, using the E-code location may be the one of the most accurate methods to identify farm injuries.…”
Section: State Trauma Registriesmentioning
confidence: 96%